2020
DOI: 10.1002/ajh.25878
|View full text |Cite|
|
Sign up to set email alerts
|

Risk‐based, response‐adapted therapy for early‐stage extranodal nasal‐type NK/T‐cell lymphoma in the modern chemotherapy era: A China Lymphoma Collaborative Group study

Abstract: We aimed to determine the survival benefits of chemotherapy (CT) added to radiotherapy (RT) in different risk groups of patients with early‐stage extranodal nasal‐type NK/T‐cell lymphoma (ENKTCL), and to investigate the risk of postponing RT based on induction CT responses. A total of 1360 patients who received RT with or without new‐regimen CT from 20 institutions were retrospectively reviewed. The patients had received RT alone, RT followed by CT (RT + CT), or CT followed by RT (CT + RT). The patients were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 43 publications
1
46
0
Order By: Relevance
“…Furthermore, there is an urgent requirement to identify patients at high risk of early progression who would benefit from innovative treatment strategies. Following the achievement of PFS24, research for ENKTCL survivors should focus on lessintensive surveillance, long-term treatment toxicity, quality of life, and other outcomes [34,37,38]. Previous studies, mainly using the randomized controlled trial (RCT) or real-world data, have demonstrated that the surrogate endpoints of EFS and PFS are strongly related to OS at both trial-and individual-level in different lymphoma subtypes [26-29, 32, 39-41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, there is an urgent requirement to identify patients at high risk of early progression who would benefit from innovative treatment strategies. Following the achievement of PFS24, research for ENKTCL survivors should focus on lessintensive surveillance, long-term treatment toxicity, quality of life, and other outcomes [34,37,38]. Previous studies, mainly using the randomized controlled trial (RCT) or real-world data, have demonstrated that the surrogate endpoints of EFS and PFS are strongly related to OS at both trial-and individual-level in different lymphoma subtypes [26-29, 32, 39-41].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there is an urgent requirement to identify patients at high risk of early progression who would benefit from innovative treatment strategies. Following the achievement of PFS24, research for ENKTCL survivors should focus on less-intensive surveillance, long-term treatment toxicity, quality of life, and other outcomes [ 34 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16][17][18] Given favorable outcomes with upfront radiotherapy for early-stage ENKTCL, adding chemotherapy to radiotherapy conferred survival benefit for intermediate-and high-risk patients but not for low-risk patients. 22,23 A variety of ASP-based or PLA-based regimens have been used as the appropriate CMT approach. [24][25][26][27][28][29][30][31][32][33][34][35][36][37] There are no comparative data describing the benefit of ASP-based regimens over non-ASP-based regimens for early-stage ENKTCL.…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…The sequencing strategy for chemotherapy and radiotherapy in early-stage ENKTCL varies across countries and between collaborative study groups. 11,23,46,47 In a recent CLCG study of 1360 NRI-stratified early-stage patients, the sequence and optimal cycles of non-anthracycline-based chemotherapy have been especially addressed in the setting of radiotherapy. 23 For intermediate-and high-risk patients treated with sequential chemoradiotherapy, radiotherapy-first CMT showed similar 5-year OS (77.7% versus 72.4%; P ¼ 0.290) and PFS (67.1% versus 63.1%; P ¼ 0.592) to chemotherapy-first CMT.…”
Section: Sensitivity Analysismentioning
confidence: 99%
See 1 more Smart Citation